2021
DOI: 10.22364/adz.57.07
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 epidēmijas ietekme uz gados vecāku cilvēku veselību Latvijā

Abstract: Lielāka varbūtība piedzīvot psihoemocionālos traucējumus ir sievietēm, kā arī cilvēkiem, kuri savu veselības stāvokli vērtē kā sliktu vai drīzāk sliktu un kuri ir vai jūtas vientuļi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Latvia and Iceland are two countries that might have different levels of social isolation due to various factors such as culture, geography, population, and COVID-19 pandemic measures. In Latvia, the COVID-19 pandemic has impacted social connections, as measures such as lockdowns, and restrictions on gatherings have limited opportunities for in-person interactions [21]. The COVID-19 pandemic has had a similar impact on social interactions in Iceland as in Latvia, but the strong community ties may have helped mitigate the effects of social isolation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Latvia and Iceland are two countries that might have different levels of social isolation due to various factors such as culture, geography, population, and COVID-19 pandemic measures. In Latvia, the COVID-19 pandemic has impacted social connections, as measures such as lockdowns, and restrictions on gatherings have limited opportunities for in-person interactions [21]. The COVID-19 pandemic has had a similar impact on social interactions in Iceland as in Latvia, but the strong community ties may have helped mitigate the effects of social isolation.…”
mentioning
confidence: 99%
“…Studies have shown that older adults who participate in regular social activities and have strong relationships with family and friends are more likely to maintain better physical and cognitive health and experience less depression and loneliness [21]. This article is an outcome of the strategic EEA initiative, aiming to strengthen bilateral relations between Latvia and Iceland in a project called Modelling of the Impact of Covid-19 on Public Health of Elderly People in Latvia and Iceland.…”
mentioning
confidence: 99%
“…Estonia and Latvia, for instance, experience elevated levels of loneliness attributed to financial hardships and disrupted family communications (4,14). Latvia, in particular, has shown a linkage between increased loneliness and factors like heightened irritability and reduced familial contact (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%